Answer:
We conclude that:
(gºf)(4) = g(f(4)) = g(6) = 6
Step-by-step explanation:
Given
![f(x) = 2x - 2](https://tex.z-dn.net/?f=f%28x%29%20%3D%202x%20-%202)
![g(x) = x](https://tex.z-dn.net/?f=g%28x%29%20%3D%20x)
We have to determine (gºf)(4).
(gºf)(4) = g(f(4))
f(4) = 2(4)-2
= 8 - 2
= 6
Thus,
(gºf)(4) = g(f(4)) = g(6) = 6
Therefore, we conclude that:
(gºf)(4) = g(f(4)) = g(6) = 6
-9,-5, -1, 10 is the right order
Y=(-x*x)-4x+3
y=-(x^2+4x-3)
4+y=-(x^2+4x+4)+3
y+4=-(x-2)^2.) +3
-4. -4
y=-((x-2)^2)-1
Answers:
Vertex: (2,-1)
AOS:x = 2
Domain: All Real Numbers
Range:[-1,Infinity)
Answer:
Option (1)
Step-by-step explanation:
By using triangle sum theorem in the given triangle,
(5x - 7)° + (11x - 4)° + (3x + 1)° = 180°
(5x + 11x + 3x) - (7 + 4 - 1) = 180
19x - 10 = 180
19x = 190
x = 10
Therefore, (3x + 1)° = 30 + 1
= 30°
(11x - 4)° = 110 - 4
= 106°
(5x - 7)° = 43°
Therefore, Option (1) will be the correct option.
Eighty seven written in standard form would be...
80 + 7 = 87
Good Luck! :)